2003
DOI: 10.1101/gad.1116203
|View full text |Cite
|
Sign up to set email alerts
|

Local regulation of fat metabolism in peripheral nerves

Abstract: We comprehensively analyzed gene expression during peripheral nerve development by performing microarray analyses of premyelinating, myelinating, and postmyelinating mouse sciatic nerves, and we generated a database of candidate genes to be tested in mapped peripheral neuropathies. Unexpectedly, we identified a large cluster of genes that are (1) maximally expressed only in the mature nerve, after myelination is complete, and (2) tied to the metabolism of storage (energy) lipids. Many of these late-onset genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
222
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(244 citation statements)
references
References 61 publications
18
222
2
2
Order By: Relevance
“…49 To our knowledge, there is no specific studies so far about the impact of the SREBP pathway in myelination in the central nervous system, but several studies have demonstrated the importance of this pathway in the peripheral myelination of axons. 50,51 The present implication of SREBF1 and SREBF2 as genetic susceptibility factors in schizophrenia further underscores the importance of lipid biosynthesis and myelination in the pathophysiology of schizophrenia.…”
Section: Abnormalities In Myelination and Lipid Biosynthesis In Schizmentioning
confidence: 85%
“…49 To our knowledge, there is no specific studies so far about the impact of the SREBP pathway in myelination in the central nervous system, but several studies have demonstrated the importance of this pathway in the peripheral myelination of axons. 50,51 The present implication of SREBF1 and SREBF2 as genetic susceptibility factors in schizophrenia further underscores the importance of lipid biosynthesis and myelination in the pathophysiology of schizophrenia.…”
Section: Abnormalities In Myelination and Lipid Biosynthesis In Schizmentioning
confidence: 85%
“…In the case of myelinating cells this involves downregulation of a large number of genes related to myelination (reviewed in Jessen and Mirsky, 2005;Mirsky et al, 2008;Scherer and Salzer, 2001). This includes enzymes that provide for cholesterol synthesis, structural proteins such as P 0 , myelin basic protein (MBP), and membrane associated proteins such as myelin associated glycoprotein (MAG) and periaxin (Buchstaller et al, 2004;D'Antonio et al, 2006;Leblanc et al, 2005;Nagarajan et al, 2001Nagarajan et al, , 2002Verheijen et al, 2003). This switch-off is accompanied by the activation of another group of molecules, most of which are normally found on immature cells prior to myelination.…”
Section: Schwann Cell Dedifferentiation During Wallerian Degenerationmentioning
confidence: 99%
“…Myelination requires the activation and high-level expression of myelin-specific genes, and the production of vast quantities of myelin membrane (Nagarajan et al, 2002;Verheijen et al, 2003). The process of myelination results in a huge increase in the size of a Schwann cell, particular of its membrane surface area, which was estimated to increase within a few days up to several thousand fold.…”
Section: Nrg1 and Schwann Cell Myelinationmentioning
confidence: 99%